ANALISIS PRAKTIK JAMINAN PERSONAL DI BMT (BAITUL MAAL WATTAMWIL) - Ahmad Mufarrihun (Al Hikmah: Jurnal Studi Keislaman, 2011)
Abstract: Baitul maal wattamwil (BMT) is one of supporting the economic activities of small communities based on shari'ah. To improve the quality and quantity of service to the community, BMT has a financing product with the requirements of the prospective borrower (customer) must provide collateral. Guarantee or borgtocht is a separate contract type among other contracts. And “borg” should be distinguished from "collateral material." While in concept this borgtocht guarantee a person or warranty is given is not the object but rather "individuals" that a third party who does not have anything of interest to both the debtor and creditor with volunteer is ready to give himself to serve as collateral to the debtor. In terms of guarantees provided in the form of a statement that the debtor can be trusted to carry out the agreed obligations, in conditions; if the debtor does not execute the borrower may be willing to implement its own obligations. With the requirement that the guarantee had been given person to a creditor means he has bound itself to implement the treaty obligation if the debtor does not carry it out later. The practice of pesonal guarantees on the TMB in accordance with the rule of law in Indonesia. The existence of the guarantee (kafalah) proves this is as good form from the Financial Institutions who want to help prospective customers who need the help of borrowing capital, and the important thing here is the prospective customer must be ready to assume the debt in accordance with the provisions that have been set or agreed upon by both parties.